2021
DOI: 10.1002/jum.15900
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Strain Elastography and Contrast‐Enhanced Ultrasound in Predicting the Efficacy of Neoadjuvant Chemotherapy for Breast Cancer: A Nomogram Integrating Ki‐67 and Ultrasound Features

Abstract: Objectives-To explore whether conventional elastography and contrast-enhanced ultrasound (CEUS) combined with histopathology can monitor the efficacy of neoadjuvant chemotherapy (NAC) for breast cancer (BC), and develop a Nomogram prediction model monitoring response to NAC.Methods-From February 2010 to November 2015, 91 BC patients who received NAC were recruited. The maximum diameter, stiffness, and CEUS features were assessed. Core biopsy, surgical pathology immunophenotype, and Miller-Payne (MP) evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The occurrence, progress, metastasis, and response to a breast cancer drug is a complex process. Previous studies showed better performance in predicting pathological response when combined with US features and Ki-67 [14]. These findings further revealed that imaging biomarkers combined with pathological indicators may acquire better progress.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The occurrence, progress, metastasis, and response to a breast cancer drug is a complex process. Previous studies showed better performance in predicting pathological response when combined with US features and Ki-67 [14]. These findings further revealed that imaging biomarkers combined with pathological indicators may acquire better progress.…”
Section: Discussionmentioning
confidence: 55%
“…Early and accurate selection of patients most likely to benefit from NAC is essential and can help patients avoid ineffective treatment and seize the best time for surgery. Primary studies on the association between breast US and response to NAC have paid attention to the changes in lesion size [14]. Indeed, there were limits to this approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous clinical SEL applications and studies were found to evaluate diagnosis and assessment of changes in tissue stiffness and elasticity in pathological conditions. [9][10][11][12][13][14] However, clinical utility of elastography has been infrequently studied in LE and has not been evaluated with tendon thickness.…”
Section: The Ultrasound Elastography Findings In Lateral Epicondyliti...mentioning
confidence: 99%
“…Several studies have examined the multidimensional features of tumor tissues using imaging parameters, such as ultrasound, 18 F-FDG PET/CT, and magnetic resonance imaging (MRI) scanning, to predict breast cancer patients’ responses to treatment and prognosis early ( 16 - 18 ). Changes in the maximum size of the breast cancer combined with ultrasonography can be informative in predicting NAC efficacy and evaluating residual lesions ( 19 ). Notably, the volumetric parameters of 18 F-FDG PET/CT before NAC, such as the metabolic tumor volume and total lesion glycolysis, are significantly correlated with the disease-free survival of breast cancer patients ( 20 ).…”
Section: Introductionmentioning
confidence: 99%